The Mediating Role of Academic Self-Regulation in the Relationship between Parenting Dimensions and Academic Procrastination - Malahat Amani; Mohamad Mahdi Arbabi (Shiraz University of Medical Sciences, 2020)
Background: Academic procrastination can be influenced by personality and family factors. The purpose of this study was to investigate the mediating role of academic self-regulation in the relationship between parenting dimensions and academic procrastination among elementary students. Methods: The method used in this study was correlation. The statistical population included all male students from the second period of elementary school in Garmeh city, Iran. Through cluster sampling, we selected a number of 278 male students. Data collection instruments were Academic Procrastination Scale, Academic Self-Regulation Questionnaire, and Parenting Style Scale. We finally analyzed the data via structural equation modeling. Results: The results showed that paternal responsiveness (r=-0.29), paternal demandingness (r=-0.34), maternal responsiveness (r=-0.24), and maternal demandingness (r=-0.34) significantly correlated with academic procrastination (P<0.0001). Furthermore, paternal responsiveness (r=0.28), paternal demandingness (r=0.25), maternal responsiveness (r=0.30), and maternal demandingness (r=0.28) were significantly associated with academic self-regulation (P<0.0001). Academic self-regulation also had a relationship with academic procrastination (r=-0.24, P<0.0001). The results of structural equation modeling showed that academic self-regulation had a mediating role in the association between parenting dimensions and academic procrastination (RMSEA=0.037). Conclusions: Parents with appropriate control and responsiveness promote the academic self-regulation of their children and prevent academic procrastination.